Determinants of joint effusion in tarsocrural osteochondrosis of yearling Standardbred horses - Bertuglia, Andrea; Pallante, Marcello; Pagliara, Eleonora; Valle, Daniela; Bergamini, Lara; Bollo, Enrico; Bullone, Michela; Riccio, Barbara (Frontiers in Veterinary Science, 2024)
Standardbreds, with different fragment localization and size. Clinically, it is characterized by variable synovial effusion in the absence of lameness, whose determinants are ill-defined. We hypothesised that localization and physical characteristics of the osteochondral fragments like dimensions, multifragmentation, and instability influence joint effusion and correlate with synovial markers of cartilage degradation and inflammation. Clinical data, synovial fluid and intact osteochondral fragments were collected from 79 Standardbred horses, aged between 12 to 18 months, operated for tarsocrural OCD. The severity of tarsocrural joint effusion was assessed semiquantitatively. The osteochondral fragment site was defined radiographically at the distal intermediate ridge of the tibia (DIRT), medial malleolus (MM) of the tibia, and/or lateral trochlear ridge (LTR) of the talus. Size, stability, and arthroscopic appearance (unique or multi-fragmented aspect) of the fragments were determined intraoperatively. Synovial concentrations of C-terminal cross-linked telopeptides of type II collagen (CTX-II), leukotriene B4 (LTB4), and prostaglandin E2 (PGE2) were quantified. Tarsocrural synovial effusion was significantly affected by localization and stability of the fragments, with MM-located and unstable fragments being associated with highest joint effusion. Concentrations of CTX-II, LTB4, and PGE2 positively correlated with the severity of synovial effusion. This study underlines characteristics of the osteochondral fragments determining higher synovial effusion in OCD-affected tarsocrural joints and suggests both inflammation and extra-cellular matrix degradation are active processes in OCD pathology.